The Development of Urban Farming: Systematics Literature Review - Dalimunthe, Maulana Andinata; Ohorella, Noviawan Rasyid; Nasution, Nabila Fahira (Journal of Peasants' Rights, 2023)
The development of urban farming continues to grow, encouraging the emergence of a joint movement in creating food security, building the environment, economy, and community empowerment. This development trend has also made urban farming one of the leading programs in building food security. This research aims to understand the relevance of urban farming development. The method used is bibliometric analysis in looking at the development of research with the keyword "urban farming. data taken from 2010-2023. The results show that urban farming is considered to be an effective way to improve food security and economic conditions in urban areas. Urban farming has the potential to provide positive impacts in various aspects, economic, social, and environmental. As a commodity production, urban farming tends to be concerned with distribution, marketing and land area. The diversity of literature places urban farming as having development potential that leads to aspects of food security and environmental effects.